Working from home and mental health: Before and during the COVID-19 pandemic - Anam Bilgrami (Global Labor Organization (GLO), 2023)
Robust evidence on working from home and mental health is lacking, with recent concerns it may blur work-home boundaries. Working from home was discretionary and less intensive in pre-pandemic years, while during the pandemic, it was often intensive and 'mandated'. I estimate the relationship between working from home and mental health via fixed-effects and instrumental variable (IV) estimation. I find no evidence that working from home harmed mental health, on average, pre-pandemic, with IV estimates suggesting potentially improved health. Conversely, working from home may have deteriorated mental health during the pandemic, potentially due its 'forced', intensive nature during this time.
Keywords: D00; I18; J81; 330; mental health; working from home; worker wellbeing; instrumental variable